Implementation of Lean Management in Public Administration to Improve the Efficiency of Government Services - Madjid, Udaya (Journal of Governance, 2025)
Public administration plays an important role in giving effective and efficient service to society. However, various obstacles like complex bureaucracy and waste source power, as well as suboptimal service processes, often becomeconstraints in increasing the quality of service in government. This research aims to analyze the implementation of the lean management concept in administration for public use to increase the efficiency of the government's service. This research uses a qualitative approach with a descriptive method. Data collected through interviews, observations, and analysis document the identification of the implementation of lean management principles. Research results show that implementation of lean management in public administration is effective in increasing efficiency in government service. With reduced waste, simplified bureaucratic processes, and optimized source power, the method speeds up decision-making as well as increasing responsiveness to the needs of society. In addition, the implementation of Kaizen principles allows for sustainable repair through regular evaluation and innovation, having a big impact in the long term. The research results also revealed that training employees in Lean principles does not only increase technical skills but also encourages pattern thinking that is more proactive and innovative. Evaluating sustainable performance based on indicators like time settlement tasks and satisfaction in society becomes a main factor in evaluating the effectiveness of changes implemented. With transparency and culture supportive work repair sustainable, bureaucracy can develop into a more modern, efficient, and interest-oriented system for the public.